2012
DOI: 10.1097/01.naj.0000411176.15696.f9
|View full text |Cite
|
Sign up to set email alerts
|

Original Research

Abstract: More attention must be paid to the health of the nursing workforce to positively influence the quality of patient care and patient safety and to control costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
105
1
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(122 citation statements)
references
References 1 publication
3
105
1
13
Order By: Relevance
“…In our opinion, showing up to work while ill could be a sign of commitment as discussed earlier, and a sing of fear of losing the job when being absent too often. Nevertheless, one could also see presenteeism as a risk of poor performance due to illness and a sign of lost productivity [21]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our opinion, showing up to work while ill could be a sign of commitment as discussed earlier, and a sing of fear of losing the job when being absent too often. Nevertheless, one could also see presenteeism as a risk of poor performance due to illness and a sign of lost productivity [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, existing studies have highlighted the magnitude of presenteeism not only by its cost of lost productivity, but also by negatively affecting quality patient care [21]. While various hospital studies in Europe and the US have examined the prevalence of presenteeism (ranging from 21.9 to 62.0%) and its associated factors [14,19,21], evidence from nursing home settings is scarce. Although the relationships between absenteeism and presenteeism are unclear, Kristensen [22] argued convincingly that both behaviors are outcomes of the same decision process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, this issue has received modest attention (33)(34)(35), especially in Croatia (30), and the main objective of our study was to establish the association between presenteeism and absenteeism on the one hand and patient safety culture on the other. We also wanted to check again our previous negative findings (30) -no association between presenteeism and patient safety culture -on a much larger sample.…”
mentioning
confidence: 99%
“…Presenteeism implies limited job performance due to a health problem (1)(2)(3)(4). Research has shown that in occupations such as nursing, poor performance at work can have serious consequences for patient safety (5)(6)(7). Patient safety culture (PSC) is a set of individual and group values, attitudes, perceptions, competencies, and behavioural patterns towards health and safety (8).…”
mentioning
confidence: 99%